Career Development and Progression of Early Career Academics in Political Science: A Gendered Perspective. (February 2021) - Briscoe-Palmer, Shardia; Mattocks, Kate
In this article, we examine the career development and progression of Early Career Academics in the discipline of political science in the UK. The primary focus is to explore whether and to what extent career development is gendered. With data from a survey of Early Career Academics as well as semi-structured interviews, the article shares personal experiences of professional development, exposing the challenges women in the profession face, including the gendered aspects of networking and mentoring, as well as broader issues of isolation, exclusion, and discrimination. These challenges are compounded by the structural contexts of UK Higher Education.